Mapping Area Of Potential Arresting Rajungan (Portunus pelagicus) In Medan Belawan Waters, North Sumatera Province - Fuadi, Afdhal; Harahap, Yuni Angraini; Miswar, Edy; Arif, Muhammad (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
Crab (Portunus pelagicus) is one of the fishery commodities that has high economic value, but fishermen in the waters of Medan Belawan still have difficulty in determining the location of the fishing area. Therefore, information is needed regarding the condition of potential arrest areas in an effort to speed up the trip of arrest operations and reduce fuel consumption. The purpose of this study is to map the distribution of sea surface temperature and chlorophyll-a as well as crab catches and also to analyze potential crab fishing areas. The method used is a survey method by recording the coordinates of the fishing area and the number of catches. Sea surface temperature and chlorophyll-a are obtained by downloading MODIS satellite imagery. The analysis used in this study is a linear regression analysis that serves to see the influence of sea surface temperature and chlorophyll-a on crab catches. The results obtained were the distribution of SPL and chlorophyll-a in Medan Belawan waters during February varied greatly, SPL ranged from 24.13ºC to 29.67ºC with an average value of 27.73ºC. While chlorophyll-a ranged from 0.11 mg/m3 to 3.52 mg/m3 with an average value of 1.613 mg/m3. The catch of crabs during February reached 6,253 kg, with the most catches of 2,380 kg, namely on February 18-25 and at least 264 kg on January 25 to February 1. The results of the analysis of the indicators of estimating the potential area of crabs show that those that are included in the potential category are KM. Khadijah, KM. Sifolin-folin 012, KM. Lugage, KM. Maduma 05, KM. SS XIII, KM. Aura, and KM. Malika Pala 1, while others fall into the potential medium category.